Cauliflower-like exophytic mass on the skin: polypoid melanoma. Clinical, dermoscopic, and histologic features, - Ambra Di Altobrando; Annalisa Patrizi; Emi Dika; Francesco Savoia (Sociedade Brasileira de Dermatologia, 2020)
Abstract Polypoid melanoma is a variant of nodular melanoma, whose poor prognosis depends on its thickness and the presence of ulceration at the time of diagnosis. The authors report two cases of polypoid melanoma, presenting as broad, cauliflower-like, polypoid masses. Dermoscopy was characterized by a multicolored pattern, atypical polymorphic vessels, and the fiber sign. Clinical and dermoscopic features can help to diagnose polypoid melanoma and exclude other possible differential diagnoses. However, histology remains mandatory to confirm the diagnostic suspicion.